Acute kinematics changes in marathon runners using different footwear - Socorro Amorim Soares, T.; Fonseca de Oliveira, C.; Pizzuto, F.; Garganta, R. M.; Vila-Boas, J. P.; da Anunciação Paiva, M. C. (Journal of Sports Sciences, 2018)
The effects of running with or without shoes on injury prevention have been extensively studied, and several investigations have assessed biomechanical differences between them. However, findings are not consensual and further insights on biomechanical load associated with differently shod or barefoot conditions may be needed. This study aimed to observe if habitually shod marathon runners show acute alterations when running barefoot or with minimalist shoes, and to determine whether the running kinematical adaptations of wearing minimalist shoes were similar to barefoot running. Twelve male marathon runners ran on the treadmill at their average marathon pace in different footwear conditions: habitual running shoes, minimalist shoes, and barefoot. High-resolution infrared cameras and visual 3D software were used to assess kinematic data. The following parameters were studied: foot strike angle, cycle time, stance time, normalized stride length, hip, knee, and ankle angular position at initial contact, and their respective range-of-motion (ROM) during stance phase. Contrary to the expectations, it was found that highly trained habitually shod elite marathon runners changed their lower limb kinematic pattern both when running barefoot or wearing minimalist shoes. Minimalist shoes showed a trend towards intermediate biomechanical effects between running with and without shoes.